BALINESE INTEREFERENCE OF ENGLISH NEWS ANCHOR - Made, Suamba; Wikarto, B.; Dewi, Ni Putu Ayu Kartika Sari (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2023)
The presence of English in Indonesian leads bilingualism and multilingualism. Bilingualism and multilingualism community cannot avoid using interference because it is the effect of a first language on their production second language. Interference occurs in any linguistics aspects likes phonology, morphology, syntax and semantic. Based on the analysis on the news entitled “The World Deepest Under Water Christmas Tree- New World Record Set at 37.5 meters” which has aired on Bali Channel Program, found that any interference occurred in the aspect of phonology, morphology, syntax and semantic. The interference was caused by lack of bilingual ability where first language acquisition interferes in producing second language and ignorance of grammatical structure of the second language.